Pengaruh Komunikasi Interpersonal Dokter Gigi-Pasien terhadap Tingkat Kepuasan di Poli Gigi Puskesmas Jember (The Influence of Interpersonal Communication of Dentist-Patient Satisfaction Rate in the Dental Poly of Health Center in Jember) - Galdhisia Devita Caresya; Zahara Meilawaty; Hestieyonini Hadnyanawati (Pustaka Kesehatan, 2015)
Interpersonal communication dentist patient is cooperative relation between dentist and patient face-to-face, either verbally or non verbally. Success of interpersonal communication of dentist-patient results in convenience and satisfaction for patients or dentists. The purpose of this study was to see whether there was an influence of interpersonal communication dentist to patient satisfaction in the dental poly of health center in Jember. This research was an observational analytic with cross sectional approach. Its used purposive sampling technique. The study was conducted in 11 health center in Jember, total subject were 398 respondents. Measuring instrument of study was a questionnaire. Results of the chi square test for the influence of interpersonal communication of dentist-patient satisfaction rate in the dental poly of health center in Jember was p = 0.000 [p < α (0.05)]. This showed there were influence of interpersonal communication toward patient satisfication in dental poly in Jember. Keywords: Dentist, Interpersonal Communication, Patient, Satisfaction